Corrosion Behavior of Copper and Carbon Steel in Acidic Media (Baghdad Science Journal, 2014)
The corrosion behavior of copper and carbon steel in 1M concentration of hydrochloric acid (HCl) and sulphuric acid (H2SO4) has been studied. The corrosion inhibition of copper and carbon steel in 1M concentration of hydrochloric acid (HCl) and sulphuric acid (H2SO4) by Ciprofloxacin has been investigated. Specimens were exposed in the acidic media for 7 hours and corrosion rates evaluated by using the weight loss method. The effect of temperature (from 283 ºK to 333 ºK), pH (from 1to 6), inhibitor concentration (10-4 to 10-2) has been studied. It was observed that sulphuric acid environment was most corrosive to the metals because of its oxidizing nature, followed by hydrochloric acid. The rate of metal dissolution increased with increasing exposure time. Corrosion rates of carbon steel in the acidic media found to be higher.